Female Reproductive Hormones Alter Sleep Architecture in Ovariectomized Rats - Deurveilher, Samüel (Associated Professional Sleep Societies, LLC, 2011)
STUDY OBJECTIVES: Treating ovariectomized rats with physiological levels of estradiol and/or progesterone affects aspects of both baseline (24 h) sleep and recovery (18 h) sleep after 6 h of sleep deprivation. We have extended the analysis of these effects by examining several additional parameters of sleep architecture using the same data set as in our previous study (Deurveilher et al. SLEEP 2009;32(7):865-877). DESIGN: Sleep in ovariectomized rats implanted with oil, 17 β-estradiol and/or progesterone capsules was recorded using EEG and EMG before, during, and after 6 h of sleep deprivation during the light phase of a 12/12 h light/dark cycle. MEASUREMENTS AND RESULTS: During the baseline dark, but not light, phase, treatments with estradiol alone or combined with progesterone decreased the mean duration of non-rapid eye movement sleep (NREMS) episodes and the number of REMS episodes, while also increasing brief awakenings, consistent with the previously reported lower baseline NREMS and REMS amounts. Following sleep deprivation, the hormonal treatments caused a larger percentage increase from baseline in the mean durations of NREMS and REMS episodes, and a larger percentage decrease in brief awakenings, consistent with the previously reported larger increase in recovery REMS amount. There were no hormonal effects on NREMS and REMS EEG power values, other than on recovery NREMS delta power, as previously reported. CONCLUSIONS: Physiological levels of estradiol and/or progesterone in female rats modulate sleep architecture differently at baseline and after acute sleep loss, fragmenting baseline sleep while consolidating recovery sleep. These hormones also play a role in the diurnal pattern of NREMS maintenance. CITATION: Deurveilher S; Rusak B; Semba K. Female reproductive hormones alter sleep architecture in ovariectomized rats. SLEEP 2011;34(4):519-530.